CHARACTERISTICS OF METHODOLOGY OF PERFORMANCE OF PHYSICAL EXERCISES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Xayitboev Nabijon Sheralievich (Galaxy International Interdisciplinary Research Journal, 2021)
In the article, improper physical training only leads to a loss of excess energy, and as a result, life activities can be directed to more useful exercises, even the same exercise, but to do it correctly or to other useful activities. for children in educational institutions, the features of the methodology of exercise were analyzed